Pond construction for freshwater fish culture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Pond construction for freshwater fish culture: building earthen ponds by A G Coche J F Muir and T Laughlin 1995 355pp ISBN 92 5 102645 9